Agglomeration mechanism during biomass carbonization in fluidized bed / Chihiro Ohashi ... [et al.] - Ohashi, Chihiro; Iwasaki, Toshiyuki; Ito, Takuya; Suganuma, Hideki; Suzuki, Seiichi; Kojima, Toshinori (Universiti Teknologi MARA, Pulau Pinang, 2015)
Among the various energy conversion technologies of the biomass, the fluidized bed is one of the devices used for its gasification. However, we pointed out the agglomerates of the bed materials surrounding char particles are observed in the bed. In the present study we carried out pyrolysis of Japanese cypress in a small fluidized bed reactor device with nitrogen flow. After cooling down, we sieved the solid in the bed and only recovered agglomerates. Afterwards we extracted solvent-soluble organic matter with chloroform/methanol solvent from agglomerates, and its yield was determined. The residual of the extraction was again sieved, and agglomerates yield after extraction and reduction in the agglomeration yield were determined. Agglomerates after extraction were incinerated in an electric furnace and determined solvent-insoluble organic matter yield. Finally, the relation between solvent-soluble organic matter yield and reduction in agglomerates yield, and that between solvent-insoluble organic matter yield and agglomerates yield after extraction were examined. From their correlations, it was suggested that agglomerates were brought by each organic matter.